2021
DOI: 10.1097/ftd.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Initial Serum C-reactive Protein Level as a Predictor of Increasing Serum Vancomycin Concentration During Treatment

Abstract: Background: Vancomycin has a narrow therapeutic window, and an increase in its serum concentration-to-dose ratio during treatment can cause renal toxicity. Therefore, this study was aimed at finding a marker to identify patients at risk of increasing serum vancomycin during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Meanwhile, Nakayama et al 7 showed that systemic clearance of vancomycin decreased in patients treated for more than 4 weeks, without any change in CrCl. In addition, Isoda et al 16 investigated the factors associated with an increased serum vancomycin concentration during treatment and found that a high CRP level at the beginning of vancomycin administration was a risk factor, independent of reduced renal function. However, the underlying mechanisms have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Nakayama et al 7 showed that systemic clearance of vancomycin decreased in patients treated for more than 4 weeks, without any change in CrCl. In addition, Isoda et al 16 investigated the factors associated with an increased serum vancomycin concentration during treatment and found that a high CRP level at the beginning of vancomycin administration was a risk factor, independent of reduced renal function. However, the underlying mechanisms have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%